Penanganan Kongesti Pada Terminal Untuk Kepentingan Sendiri (TUKS) - Sulida Erliyana; Manda Kiki Riyanto (Majalah Ilmiah Gema Maritim, 2019)
The purpose of writing this final project is to identify and explain the handling congestion at private terminal PT. Petrokimia Gresik. The method used in writing final project was an interview and literature, in this case to collect data in the form of data through observation of the object, the subject matter as well as the collection of documents and data relating to the congestion at private terminal PT. Petrokimia Gresik. Based on the result of the discussion had been obtained that the handling congestion at private terminal PT. Petrokimia Gresik, handling by planning the arrival and the departure of the vessel properly and appropriately, doing repair to the damage loading and unloading equipments, adding loading and unloading equipments on each vessels. The conclusion of handling congestion at private terminal PT. Petrokimia Gresik was very essential. So, a vessel which was going to discharge of cargo at private terminal will not undergo demurrage and hopefully become despatch.